In vivo metabolism study of (R)‐bambuterol in humans using ultra high performance liquid chromatography with tandem mass spectrometry. Issue 15 (27th June 2016) - Zhou, Ting; Zeng, Dan; Zhao, Ting; Yang, Yang; Liu, Shan; Wu, Jie; Xu, Ling; Tan, Wen
Abstract : ( R )‐Bambuterol, a selective β2‐adrenoceptor agonist, has been approved as a new drug for the treatment of asthma and chronic obstructive pulmonary disease by the China Food and Drug Administration and is currently under phase I clinical trials. In this study, a combined method based on ultra high performance liquid chromatography with triple quadrupole mass spectrometry and ultra high performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry was employed for the identification of the major metabolites of ( R )‐bambuterol in human plasma and urine after an oral dose of 10 mg. The metabolites were separated by gradient elution program and different sample preparation methods were compared. Totally, 12 metabolites of ( R )‐bambuterol were identified, including four metabolites in plasma and all 12 metabolites in urine. Among these, four metabolites are reported for the first time. The possible metabolic pathways of ( R )‐bambuterol were subsequently proposed. The results indicated that ( R )‐bambuterol was metabolized via hydrolysis, demethylation, oxygenation, glucuronidation, and sulfation pathways in vivo. This study revealed that this combined method was accurate and sensitive to identify the possible metabolites and to better understand the metabolism of ( R )‐bambuterol in vivo.